Association Between Clinical Tests Related to Motor Control Dysfunction and Changes in Pain and Disability After Lumbar Stabilization Exercises in Individuals With Chronic Low Back Pain - Oliveira, Crystian B. [UNESP]; Pinto, Rafael Z.; Schabrun, Siobhan M.; Franco, Marcia R.; Morelhão, Priscila K. [UNESP]; Silva, Fernanda G. [UNESP]; Damato, Tatiana M. [UNESP]; Negrão Filho, Ruben F. [UNESP] (Elsevier, 2019)
Objective: To investigate whether clinical tests used to detect motor control dysfunction can predict improvements in pain and disability in patients with chronic nonspecific low back pain (LBP) who have undergone an 8-week lumbar stabilization exercise program. Study Design: A prospective cohort study. Setting: Outpatient physical therapy university clinic. Participants: Seventy people with chronic nonspecific LBP were recruited, and 64 completed the exercise program (N=64). Interventions: The lumbar stabilization program was provided twice a week for 8 weeks. Main Outcome Measures: Pain intensity (11-point numerical rating scale) and disability (Roland Morris Disability Questionnaire) and clinical tests, such as the Deep Muscle Contraction (DMC) scale, Clinical Test of Thoracolumbar Dissociation (CTTD), and Passive Lumbar Extension (PLE) test. Univariate and multivariate linear regression models were used in the prediction analysis. Results: Mean changes in pain intensity and disability following the 8-week stabilization program were −3.8 (95% confidence interval [CI], −3.2 to −4.4) and −7.4 (95% CI, −6.3 to −8.5), respectively. Clinical test scores taken at baseline did not predict changes in pain and disability at 8-week follow-up. Conclusion: Our findings revealed that the DMC scale, CTTD, PLE test, clinical tests used to assess motor control dysfunction, do not predict improvements in pain and disability in patients with chronic nonspecific LBP following an 8-week lumbar stabilization exercise program.
Keywords: Exercise therapy; Low back pain; Outcome and process assessment (health care); Rehabilitation